PENGOLAHAN AIR LINDI TPA PIYUNGAN MEMPERGUNAKAN ADVANCED OXIDATION PROCESS (AOP) DENGAN KOMBINASI OZON (O3) DAN HIDROGEN PEROKSIDA (H2O2) - Sanjaya, Tri; Hudori, Hudori (Universitas Pelita Bangsa, 2025)
Leachate is a liquid waste generated from the decomposition of solid waste in landfill sites and typically contains high concentrations of organic pollutants. This study aims to evaluate the effectiveness of an Advanced Oxidation Process (AOP) combining ozone (O₃) and hydrogen peroxide (H₂O₂) in reducing COD and TSS levels in landfill leachate. The leachate samples were collected from Piyungan Landfill, Bantul. The experiments were conducted using a batch reactor with varying doses of H₂O₂ (10, 20, 30, and 40 ml) and ozonation times of 20, 40, 60, and 80 minutes. The results showed that the highest reduction in COD reached 69% at a 40 ml dose of H₂O₂ with 60 minutes of ozonation. Meanwhile, TSS reduction reached 43% at the same dose of H₂O₂ with 80 minutes of ozonation. Based on these findings, the combination of O₃ and H₂O₂ in the AOP method is effective for treating landfill leachate, particularly for reducing COD and TSS levels.